2017
DOI: 10.1080/00365521.2017.1288756
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding gastric and duodenal ulcers: case-control study comparing angioembolization and surgery

Abstract: Mortality and rebleeding rates did not differ between TAE and surgery. With less postoperative complications, TAE should be the preferred hemostatic method when endoscopy fails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 31 publications
5
38
1
Order By: Relevance
“…For surgical salvage therapy, reported rates of rebleeding, complications, and mortality are 6.8% to 23.0%, 63.0% to 68.0%, and 18.0% to 25.0%, respectively. 6,5,[31][32][33] Although there is a lack of RCTs, TAE is associated with similar rebleeding and mortality rates (25.0%-29.0% and 12.5%-20.8%), but complication rates are reported to be lower than those of surgery (37.5%-40.6%). 6,5,[31][32][33] In our study, 30-day recurrent bleeding rate, complication rate, and mortality were 12.9%, 15.1%, and 12.1% in the OTSC group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For surgical salvage therapy, reported rates of rebleeding, complications, and mortality are 6.8% to 23.0%, 63.0% to 68.0%, and 18.0% to 25.0%, respectively. 6,5,[31][32][33] Although there is a lack of RCTs, TAE is associated with similar rebleeding and mortality rates (25.0%-29.0% and 12.5%-20.8%), but complication rates are reported to be lower than those of surgery (37.5%-40.6%). 6,5,[31][32][33] In our study, 30-day recurrent bleeding rate, complication rate, and mortality were 12.9%, 15.1%, and 12.1% in the OTSC group.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is associated with a mortality of between 14% and 29% and high complication rates. 2,5,6 Very likely, improvement of endoscopic hemostasis for recurrent bleeding directly impacts clinical outcome. Although injection of diluted adrenaline only is not adequate for hemostasis, combination with through-the-scope clips (TTSCs) or thermal methods is considered to be the standard endoscopic therapy.…”
Section: Sting Studymentioning
confidence: 99%
“…Beggs et al included 9 cohort studies (8 retrospective and 1 prospective), and similarly concluded that surgery was associated with a significantly lower risk of rebleeding, and only a marginal trend towards increased mortality. Subsequent to these first two meta-analyses, a case-control study comparing angioembolization with surgery [138] reported a trend to higher rebleeding rates following angioembolization, and a trend towards higher mortality after surgery was seen. A significantly lower rate of post-procedural complications was reported in the angioembolization cohort.…”
Section: Angiography Embolizationmentioning
confidence: 99%
“…In-hospital 60-day mortality rates were 287/2444 (11.7%, 95% CI 10.5% to 13.1%) for perforations, and 68/382 (17.8%, 95% CI 14.1% to 22.0%) for bleeding. Median (IQR) 2-year institutional volume was 12 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and 2 (1-3) for perforation and bleeding, respectively. In the exploratory analysis, age, American Society of Anesthesiology score and preoperative systolic blood pressure were associated with mortality, with no association with time from admission to operation, surgeon grade or operative approach.…”
Section: Introductionmentioning
confidence: 99%